O negócio do ócio: o teatro profissional londrino (1576-1603) - Seidl, Rodrigo (2009)
The objective of this dissertation was to investigate the ways in which Elizabethan professional theatre practice was, at the same time, a product and a producer of historical changes. Following the construction of London s first purpose-built playhouse in 1576, theatre slowly became a lucrative business run by full-time professionals. Soon after this historical development, the professional companies suffered constant attacks. These claimed that plays propagated sin and idleness among those who watched or took part in them. Through the analysis of the anti-theatrical writings and laws produced between 1576 and 1603, we observed the nature of the changes in theatrical practice in London and questioned the motives behind the attacks against the stage. We found that the process of professionalization of the London companies incorporated many of the social changes at work at the time. However, the new theatres created new social spaces in which transgressive social practices found their place beyond the City s control. Therefore, the professional theatre played an active role in making these new social values visible